Prize Effect: an analysis of the Nota Fortaleza program - da Cunha Júnior, José Maria; Brito Soares, Ricardo; Cristina Silva de Azevedo, Débora (Revista Economia Ensaios, 2024)
The purpose of this article is to analyze whether the Nota Fortaleza program fulfills its role in terms of the continuous engagement of consumers in the inspection process, since they are awarded. For this, we use a panel data model, considering different intercepts in order to control effects not observed in cross-section units. The estimated coefficients for the main indicators were statistically higher than those observed for the lagging indicators for all levels of awards, associated with a hypothesis that the contemplation in the draw affects their behavior in a future analysis window.